The relationship between motor development and social adaptability in autism spectrum disorder - Chen, YanJie; Fei, Xi; Wu, TianChen; Li, HongJuan; Xiong, NiNa; Shen, RuiYun; Wang, Ying; Liang, AiMin; Wang, Huan (Frontiers in Psychiatry, 2022)
Objectives: Autism spectrum disorders（ASD）describe a wide range of pervasive developmental disorders by core symptoms including deficits in social communication and interaction, and language disorders, as well as restricted, repetitive, and stereotyped behaviors. At the same time, some children with autism are accompanied by motor development disorder. Many studies have confirmed that the motor development impairment was significantly associated with the social problems associated with ASD. Thus, this study aimed to investigate how motor development affects social adaptability in children with ASD to provide references for early ASD intervention. Methods: The case data of children's health care were selected in 2021. Motor development was assessed with the Developmental Behavior Assessment Scale for Children Aged 0-6 Years. Social adaptability was measured using the Japanese S-M Social Living Skills Scale. Statistical analysis was conducted with SPSS 22.0 software package. Data were analyzed using chi-square tests, independent sample t-tests, and logistic regression. Results: The final 198 cases were included, 107 ASD cases, and 91 controls. The average age of participants was 3.40±1.06 years, with 3.33±1.18 years in the control group and 3.46±0.95 years in the ASD group. No statistically significant difference in age and sex was observed between the ASD and control groups. Independent sample t-test and Chi-square test showed that the children with ASD had significantly lower developmental behavior and social adaptability than the TD children (P<0.001). The logistic regression showed that the regression coefficient value of fine motor was 0.655, P<0.001. After controlling the effects of age and sex, the results showed that fine motor increased by 1 unit, and the OR value of one level decreased in social adaptability was 1.92 times. Conclusions: There is a relationship between the development of fine motor and the social adaptability of autistic children. Fine motor development can be used as an early focus in the intervention and treatment of children with ASD, as it has great importance in improving children's self-care ability and social adaptability.